Aptamers: Design, Theory, and Applications to Diagnosis and Therapy for Diseases - Sepideh Hassibian; Mahsa Amin; Seyed Mohammad Taghdisi; Elham Sameiyan; Reza Ghaffari; Mona Alibolandi; Mohammad Ramezani; Khalil Abnous; Seyed Mohsen Dehnavi (MedComm)
ABSTRACT Single‐stranded DNA or RNA entities referred to as aptamers exhibit a strong affinity and specificity for attaching to specific targets. Owing to their special properties, which include simplicity of synthesis, low immunogenicity, and adaptability in targeting a variety of substances, these synthetic oligonucleotides have garnered a lot of interest. The function of aptamers can be altered by combining them with complementary oligonucleotides “antidotes,” which are antisense to a particular aptamer sequence. Antidotes play an important role in several fields by specifically targeting the corresponding section of the aptamer. Nevertheless, even with their promising capabilities, the creation of antidotes to regulate or inhibit aptamer function continues to be a relatively unexamined field, constraining their secure and efficient application in medical environments. The review explores experimental methodologies for creating antidotes, the systematic design strategies for managing antidotes in aptamer‐based therapies, and their therapeutic efficacy in counteracting disease biomarkers. Additionally, it highlights their diagnostic applications in biosensing and imaging, offering a promising alternative to traditional antibodies. It also investigates the progress, latest innovations, and potential medical uses of aptamer–antidote combinations. Its academic value lies in bridging the gap between theoretical design and practical applications, providing researchers and clinicians with a comprehensive resource to advance aptamer‐based solutions in medicine and biotechnology.